Effect of chemical surface treatments and repair material on transverse strength of repaired acrylic denture resin - Vojdani Mahroo; Rezaei Sakineh; Zareeian Lila (Wolters Kluwer Medknow Publications, 2008)
Purpose: This study was performed to evaluate the transverse strength of a denture base resin (H), repaired with an autopolymerizing acrylic resin (A) or a visible light-curing (VLC) resin (T) following the use of three chemical solvents: methyl methacrylate monomer, aceton or chloroform. Materials and Methods: Eighty specimens (65.0 x 10.0 x 3.3 mm) of H were fabricated and stored in distilled water at 37°C for seven days. Specimens were divided into eight equal groups of 10. In each group, specimens were sectioned in the middle to create a 10 mm gap. Two groups served as controls and had no surface treatment. They were repaired with A or T materials. In the remaining six experimental groups, specimen surfaces were treated with ac for 30 sec or mma for 180 sec or ch for 5 sec. Then A or T material was placed on the treated surfaces, using the same preparation molds. After seven days′ storage at 37°C, the transverse bond strength (MPa) of the specimens was measured using a three-point bending test. A two-way ANOVA and a Tukey HSD were performed to identify significant differences ( P < 0.05). The nature of the failures was noted as adhesive, cohesive or mixed. Results: Significant differences were found between the controls and experimental groups ( P < 0.05). In the control groups, repair with A showed significantly higher strength (60.3 MPa) than those repaired with T (51.3 MPa). Mean transverse strength of experimental specimens repaired with A was (75.06 MPa) which was significantly greater than those repaired with T (67.9 MPa). Although surface treatment increased repair strength, no significant differences were detected between the effects of the chemical etchants. Conclusions: The autopolymerizing resin exhibited significantly higher repair strength than VLC resin. The transverse strength of the repaired specimens was increased significantly after chemical treatments.